2015
DOI: 10.1186/s40478-015-0267-2
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock proteins are induced during multiple sclerosis lesion development in white but not grey matter

Abstract: IntroductionThe important protective role of small heat-shock proteins (HSPs) in regulating cellular survival and migration, counteracting protein aggregation, preventing apoptosis, and regulating inflammation in the central nervous system is now well-recognized. Yet, their role in the neuroinflammatory disorder multiple sclerosis (MS) is largely undocumented. With the exception of alpha B-crystallin (HSPB5), little is known about the roles of small HSPs in disease. ResultsHere, we examined the expression of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 57 publications
1
21
2
1
Order By: Relevance
“…Blocks were screened by immunostaining sections for PLP and HLA‐DR to select regions containing CWM/CGM in controls and NAWM/NAGM in MS cases to exclude blocks containing lesions. Although increased mRNA levels of HSPB1, HSPB6 and HSPB8 have been reported previously in MS brain NAWM , no differences in HSPB or HSP16.2 protein expression were found between controls and MS patients (Supporting information, Fig. ).…”
Section: Resultsmentioning
confidence: 66%
“…Blocks were screened by immunostaining sections for PLP and HLA‐DR to select regions containing CWM/CGM in controls and NAWM/NAGM in MS cases to exclude blocks containing lesions. Although increased mRNA levels of HSPB1, HSPB6 and HSPB8 have been reported previously in MS brain NAWM , no differences in HSPB or HSP16.2 protein expression were found between controls and MS patients (Supporting information, Fig. ).…”
Section: Resultsmentioning
confidence: 66%
“…Such a specific association with the early stages of lesion development is likely to reflect the presence of more specific factors in the pathogenesis of a disease . In MS, for example, HSPB5 is strongly and selectively induced in oligodendrocytes within preactive lesions, while other sHSPs only become upregulated in active lesions when myelin damage has already occurred . This clearly points to a critical role of oligodendrocyte stress in the development of MS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the preclinical disease pathology in more detail, we have investigated the expression of αB‐crystallin, a member of the small heat shock family of proteins, as a marker of cellular stress. Previous studies of autoimmune demyelinating diseases have reported that its expression is robustly up‐regulated both in MS (Bajramovic et al, ; Peferoen et al, ) and EAE (Chabas et al, ; Ousman et al, ). In particular, αB‐crystallin has been reported to be expressed early during MS pathology, being observed within both developing lesions (Bajramovic, Lassmann, & van Noort, ) and in the normal‐appearing white matter (Van Noort et al, ), where it may represent an early stress response.…”
Section: Introductionmentioning
confidence: 99%